Dietary Protein Intake and Lean Muscle Mass in Survivors of Childhood Acute Lymphoblastic Leukemia: Report From the St. Jude Lifetime Cohort Study. Issue 7 (1st July 2016) - Boland, Alexandra M.; Gibson, Todd M.; Lu, Lu; Kaste, Sue C.; DeLany, James P.; Partin, Robyn E.; Lanctot, Jennifer Q.; Howell, Carrie R.; Nelson, Heather H.; Chemaitilly, Wassim; Pui, Ching-Hon; Robison, Leslie L.; et al.
Abstract: Background: Survivors of childhood acute lymphoblastic leukemia (ALL) are at risk for low lean muscle mass and muscle weakness, which may contribute to inactivity and early development of chronic diseases typically seen in older adults. Although increasing protein intake, in combination with resistance training, improves lean muscle mass in other populations, it is not known whether muscular tissue among survivors of ALL, whose impairments are treatment-related, will respond similarly. Objective: The aim of this study was to evaluate associations among dietary protein intake, resistance training, and lean muscle mass in survivors of ALL and age-, sex-, and race-matched controls. Design: This was a cross-sectional study. Methods: Lean muscle mass was determined with dual-energy x-ray absorptiometry, dietary information with 24-hour recalls, and participation in resistance training with a questionnaire. Participants were 365 survivors of ALL (52% male; 87% white; median age=28.5 years, range=23.6–31.7) and 365 controls with no previous cancer. Results: Compared with controls, survivors of ALL had lower lean muscle mass (55.0 versus 57.2 kg, respectively) and lower percentage of lean muscle mass (68.6% versus 71.4%, respectively) than controls. Similar proportions of survivors (71.1%) and controls (69.7%) met recommended dietary protein intake (0.8 g/kg/d). Survivors (45.4%) were less likely to report resistance training than controls (53.8%). In adjusted models, 1-g higher protein intake per kilogram of body mass per day was associated with a 7.9% increase and resistance training ≥1×wk, with a 2.8% increase in lean muscle mass. Limitations: The cross-sectional study design limits temporal evaluation of the association between protein intake and lean muscle mass. Conclusions: The findings suggest that survivors of childhood ALL with low lean muscle mass may benefit from optimizing dietary protein intake in combination with resistance training. Research is needed to determine whether resistance training with protein supplementation improves lean muscle mass in survivors of childhood ALL.